SISTEM INFORMASI MANAJEMEN DATA BEASISWA BIDIKMISI PADA UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARI (UNISKA MAB) BANJARMASIN - Mayang Sari; M. Muflih (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This research was conducted with the intent to produce an application that can manage all data of the scholarship recipient bidikmisi and can monitor student achievement of the recipient of bidikmisi so that at the time of annual monitoring from Kopertis Wilayah XI Kalimantan file owned by Islamic University of Kalimantan Muhammad Arsyad Al Banjari (UNISKA MAB) Banjarmasin Can be accessed easily and quickly. Bidikmisi scholarship has been held in UNISKA MAB since 2012 until now with the total number of recipients until the year 2015 as many as 133 students. During this time, the Bidikmisi scholarship student file received by the UNISKA MAB is stored in the form of files per student per force stored in a special wardrobe receiver bidikmisi. For that we need a system that can accommodate all data of student recipients bidikmisi scholarship in the form of digital. Seen from the problems that exist in this research, then in this study built an application to manage bidikmisi scholarship data including academic data management student recipient bidikmisi scholarship for eight semesters in order to facilitate the search for data and monitoring student achievement of learning achievement bidikmisi and minimize the risk of data loss due to the piles of physical files that had been in the closet storage. Keywords: Application manage, Bidikmisi, Scholarship